Temperature-dependent change of the electronic structure in the Kondo lattice system YbRh2Si2. (27th April 2021) - Agustsson, S Y; Chernov, S V; Medjanik, K; Babenkov, S; Fedchenko, O; Vasilyev, D; Schlueter, C; Gloskovskii, A; Matveyev, Yu; Kliemt, K; Krellner, C; Demsar, J; et al.
Abstract: The heavy-fermion behavior in intermetallic compounds manifests itself in a quenching of local magnetic moments by developing Kondo spin-singlet many-body states combined with a drastic increase of the effective mass of conduction electrons, which occurs below the lattice Kondo temperature T K . This behavior is caused by interactions between the strongly localized 4 f electrons and itinerant electrons. A controversially discussed question in this context is how the localized electronic states contribute to the Fermi surface upon changing the temperature. One expects that hybridization between the local moments and the itinerant electrons leads to a transition from a small Fermi surface in a non-coherent regime at high temperatures to a large Fermi surface once the coherent Kondo lattice regime is realized below T K . We demonstrate, using hard x-ray angle-resolved photoemission spectroscopy that the electronic structure of the prototypical heavy fermion compound YbRh2 Si2 changes with temperature between 100 and 200 K, i.e. far above the Kondo temperature, T K = 25 K, of this system. Our results suggest a transition from a small to a large Fermi surface with decreasing temperature. This result is inconsistent with the prediction of the dynamical mean-field periodic Anderson model and supports the idea of an independent energy scale governing the change of band dispersion.